Skills Development from the Point of View of Attitude Theory in Foreign Language Learning - Ramoškienė, Aldona (Acta Paedagogica Vilnensia, 2004)
The article deals with the decisive role of the students’ attitude in the development of skills in learning foreign languages at the Universities. Great variety of practically applied language teaching methods failed to fulfil expectations as no proper attention was directed towards teaching atmosphere and personalities of language teacher and learner.